The Patient Narrative for Breast Implant Illness: A 10-Year Review of the U.S. Food and Drug Administration's MAUDE Database. Issue 6 (15th September 2022) - Taskindoust, Mahsa; Bowman, Trevor; Thomas, Samantha M.; Levites, Heather; Wickenheisser, Victoria; Hollenbeck, Scott T.
Abstract : Background: There is growing recognition of a condition known as breast implant illness. Very little information exists about the diagnosis and natural history of breast implant illness. To better understand the patient experience, we surveyed the U.S. Food and Drug Administration's Manufacturer and User Facility Device Experience (MAUDE) database for narratives describing symptoms of breast implant illness. Methods: The MAUDE database was queried for all reports that included breast implant illness within the patient narrative between 2010 and 2020. A review of narratives was used to identify and summarize 36 symptoms over nine symptom classes. Event year and reporting year were summarized. Hierarchical clustering analysis using centroid components was conducted on all reported breast implant illness symptoms, and a dendrogram was created to visualize clustering. Results: During the study period from 2010 to 2020, there were 751 captured adverse event reports in the MAUDE database that referenced breast implant illness, with the first report submission in 2014. Of those reports, 60.6 percent were for silicone implants and 39.4 percent were for saline implants. The three most commonly reported symptom categories were neurologic [ n = 544 (72.4 percent)], followed by musculoskeletal [ n = 418 (55.7 percent)], and dermatologic [ n = 273 (36.4 percent)]. The top 10 symptoms, irrespective of category, include fatigue/weakness, numbness/tingling, brain fog, depression/anxiety, arthralgia, myalgia, headache, hair loss, gastrointestinal issues, and weight change. A hierarchical clustering analysis demonstrated that symptoms reported by patients clustered into two major groups. Conclusion: This study demonstrates the utility of public-facing databases, such as the Manufacturer and User Facility Device Experience database, in understanding the patient experience as it relates to breast implant illness.